PADDAS syndrome associated with hair dysplasia caused by a de novo missense variant of PUM1. Issue 6 (23rd March 2019) - Bonnemason‐Carrere, Paul; Morice‐Picard, Fanny; Pennamen, Perrine; Arveiler, Benoit; Fergelot, Patricia; Goizet, Cyril; Hellegouarch, Mélanie; Lacombe, Didier; Plaisant, Claudio; Raclet, Virginie; Rooryck, Caroline; Lasseaux, Eulalie; et al.
Abstract : PUM1 has been very recently reported as responsible for a new form of developmental disorder named PADDAS syndrome. We describe here an additional patient with early onset developmental delay, epilepsy, microcephaly, and hair dysplasia, with a de novo heterozygous missense variant of PUM1 : c.3439C > T, p.(Arg1147Trp). This variant was absent from databases and predicted deleterious by multiple softwares. The same missense variant has been reported by Gennarino et al., in a girl with much more severe epilepsy. Our report is in favor of a variable expressivity of PADDAS syndrome, and broadens the phenotypic spectrum with the description of hair dysplasia.